On the Use of Visual Methods to Understand Local Immigration Politics - Desille, Amandine (2021)
In this chapter, I present the making of an ethnographic film, which I filmed during a research project in geography carried out from 2013 to 2017 and entitled Victory Day. The chapter provides a reflection on the use of film to capture political actions, specifically the ones targeting immigrant groups. It also shows the extent to which filmmaking relates to experiences of the participants involved, and to the sensorial experience of a place. With this, it builds on previous works that have highlighted the potential of moving images to represent the sensory, experiences and intersubjectivities. Finally, it tackles the ethics of working in conflict cities, and even more specifically, when participants take a hawkish stand in that conflict.